Effect of high voltage electrostatic field treatment on the storability of postharvest ponkan fruit - WU Jue; XIE Wenhua; XU Shuting; CHEN Yezhi; CAO Jinping; WANG Yue; SUN Chongde (浙江大学学报. 农业与生命科学版)
The effects of high voltage electrostatic field (HVEF) treatment on the storability of postharvest ponkan (Citrus reticulata Blanco cv. Ponkan) fruit were studied. The results showed that, the HVEF treatment reduced the decay rate of ponkan fruit, with the single treatment at 200 kV/m for 2 h as the optimum measure. Correspondingly, the number of surface microorganisms was reduced by the HVEF treatment. The fruits treated by the HVEF had the lower weight loss rate, the respiration rate and the accumulation of ethanol, but had the higher sucrose, glucose and fructose contents than those of the control. The indole-3-acetic acid (IAA) level of fruits by the HVEF treatment was significantly elevated throughout the storage process; in addition, the abscisic acid (ABA) level was significantly elevated at the early stage of storage (30 d). The results of transmission electron microscope observation showed the structural changes in the cell of the fruit peel. In conclusion, the HVEF treatment is effective in reducing the postharvest loss and maintaining the quality of ponkan fruit through sterilization and fruit physiological regulation.